Preventing lithium-polymer (LiPo) cell fire with an embedded extinguisher - Chong, Benjamin Jie Min (Nanyang Technological University, 2023)
With the world progresses to curb carbon footprints, many researchers and engineers have developed alternative solutions to reduce carbon emissions. Lithium-containing batteries became very popular. Lithium Polymer (LiPo) batteries have been one of the top options to provide power to devices. LiPo batteries can be found in commercial Personal Mobility Devices (PMD) and Power-Assisted Bicycle (PAB) due to their high-energy density to store power and lightweight feature. In recent years, despite the safety features and measures, Singapore has seen a tremendous rise in fires related to these batteries. These fires happened for several reasons and have been perceived to cause undesirable explosions, resulting in loss of properties and lives. A cell fire extinguisher (CFE) can be embedded within the enclosure of the battery packs to put out fires before they grow. To end this, a detailed experimental procedure to evaluate the efficacy and drawbacks of CFE has been constructed in this project. An overcharging method was adopted to ignite LiPo battery explosions and the temperatures were analysed through a thermal imager. Tests were first carried out on a 1-cell LiPo battery to evaluate the consistency of the temperature profile and durations of explosion. The subsequent tests analysed the effects of CFE on a burning 1-cell LiPo battery, which includes the number of CFE needed and the distance between the CFE and the burning battery. Data and results conclude that the CFE can put out the fire in the experiments. Recommendations are given to search for the possibilities of CFE in reducing the fire spreading with various battery sizes, as well as its efficacy and drawbacks.